Byzantine monetary affairs during the 8th, 9th, 10th and 11th centuries - Athanassopoulou-Pennas, V; Athanassopoulou-Pennas, Vassiliki (1991)
﻿ The subject for this dissertation is the study of Byzantine monetary affairs from the accesion of Leo III (717) up to the beginning of Alexius I's reign (1081). The work is divided into the following main chapters: I. Gold Coinage: Taking into account documentary and fragmentary numismatic evidence new chronologies and a few new attributions are attempted. A thorough survey of the recorded types and a detailed discussion of the relevant literature is included. References to iconography, monetary reforms and minting process are made. II.Silver Coinage: A similar study, including a separate section on metrology and valuation. III.Copper Coinage: The focus is concentrated in the coinages of Michael II, Theophilus and the anonymous folles of Class A. With the aid of detailed stylistic analyses, the study of dies and then the geographical distribution of the sylistic groups, the complex problem of provincial mints is discussed. The study is supplemented by four Appendices. Appendices I-III include a descriptive catalogue of 378 copper coins of Michael II and Theophilus upon which the stylistic analysis is based. Appendix IV contains catalogues of hoards and stray finds of Anonymous folles of Cl.A from Greece. Yugoslavia, Bulgaria, Romania and Asia Minor. IV. Monetary Circulation. A detailed survey of the attested evidence from all the areas under Byzantine dominion is included. On the basis of hoards and stray-finds the trends of the circulation in Greece are described. This study is supplemented by Appendix V, where a corpus of 122 coin hoards is presented.